2022
DOI: 10.1186/s12936-021-04026-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and methods for a quasi-experimental pilot study to evaluate the impact of dual active ingredient insecticide-treated nets on malaria burden in five regions in sub-Saharan Africa

Abstract: Background Vector control tools have contributed significantly to a reduction in malaria burden since 2000, primarily through insecticidal-treated bed nets (ITNs) and indoor residual spraying. In the face of increasing insecticide resistance in key malaria vector species, global progress in malaria control has stalled. Innovative tools, such as dual active ingredient (dual-AI) ITNs that are effective at killing insecticide-resistant mosquitoes have recently been introduced. However, large-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…Insecticides from additional classes including the neonicotinoids and pyrrole, are now being incorporated into vector control products such as indoor residual sprays and ITNs and work is ongoing to assess the susceptibility of these laboratory colonies to these active ingredients. Encouragingly, all strains appear susceptible to the pyrrole chlorfenapyr, used in the ITN IG2 ® (BASF, Germany) that is being deployed in pilot schemes in Burkina Faso [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insecticides from additional classes including the neonicotinoids and pyrrole, are now being incorporated into vector control products such as indoor residual sprays and ITNs and work is ongoing to assess the susceptibility of these laboratory colonies to these active ingredients. Encouragingly, all strains appear susceptible to the pyrrole chlorfenapyr, used in the ITN IG2 ® (BASF, Germany) that is being deployed in pilot schemes in Burkina Faso [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, current National Malaria Control Program activities to expand indoor residual spraying activities (from 2-8 districts last decade to 12-15 districts this decade) and to introduce synergistic insecticide impregnated nets (piloted in 2019-2020 with distribution planned for 2023 [31]) are likely to reduce biting rates and case numbers in the coming years. A recent pilot study in rural part of Gasabo district with high malaria risk showed that larviciding activity had a moderate effect on reducing incidence; NMCP also expects to expand larviciding as part of a new set of malaria control activities.…”
Section: Discussionmentioning
confidence: 99%
“…This study is leveraging several planned intervention studies, including cross-sectional household surveys (modified malaria indicator surveys) at the district or village level that collect parasite prevalence data among children under 5 years (and other age groups as well, depending on country-specific epidemiology and national malaria control programme priorities). In Burkina Faso, Mozambique, and Nigeria, study activities are aligned with surveys from the New Nets Project, an observational quasi-experimental study that is evaluating the cost-effectiveness of various types of insecticidetreated nets [16].…”
Section: Study Settings and Locationmentioning
confidence: 99%
“…15 National Malaria Elimination Program, Abuja, Nigeria. 16 Faculté Des Sciences de La Santé/Université d' Abomey Calavi, Godomey, Benin. 17 PATH, Maputo, Mozambique.…”
Section: Abbreviationsunclassified